Matching Electricity Footprint of Commercial Customers to Industry-Specific Profiles for Enhanced Power Management - Tomasz Zabkowski; Krzysztof Gajowniczek; Jacek Brożyna; Grzegorz Matejko (Energies)
This paper presents a method for assigning the electricity consumption profiles of 10,129 commercial customers in Poland to specific industry profiles. The customer consumption data were compared with eight industry profiles for which the business activities were known. Additionally, a clustering analysis was conducted to identify homogeneous groups among the customers. The aim of this research was to develop a simple yet reliable approach for matching electricity usage patterns with specific profiles while relating them to the overall profile of the Polish power system. This offers valuable insights into how commercial customers utilize electricity and their actual contributions to the system’s peak load, which can further contribute to more efficient energy management and production planning within the Polish power system. Furthermore, the clustering analysis provides a new understanding of consumption patterns, allowing for better predictions of peak load behavior and more refined energy management strategies across sectors.